Non-traditional Lipid Profile and Obstructive Coronary Artery Disease Based On CAD-RADS Score - Munita, Fatihatul Firdaus; Kusumawardhani, Nuraini Yasmin; Achmad, Chaerul; Astuti, Astri; Muthiah, Azizah (The Indonesian Heart Association, 2025)
Background: The association between dyslipidemia and coronary artery disease (CAD) is undisputable. Current evidence suggests that, in comparison to conventional lipid parameters, a comprehensive non-traditional lipid profile serves as a more robust predictor of CAD. The evidence regarding the correlation between nontraditional lipid profile and severity of coronary lesions, as measured by the coronary artery disease-reporting and data system (CAD-RADS) score by Coronary Computed Tomography Angiography (CCTA), is still scarce. This study aimed to elaborate on the association between those parameters. Understanding these associations may improve risk stratification and management in CAD patients. Methods: A cross-sectional single-center study was conducted in a large population of patients with suspected CAD. Data were obtained from medical records between January 2020 and February 2024. The CAD-RADS score was stratified into three groups: CAD-RADS 0 (no CAD), CAD-RADS 1-2 (stenosis <50%, classified as non-obstructive CAD), and CAD-RADS ≥3 (stenosis ≥50% in ≥1 coronary segment, classified as obstructive CAD). Logistic regression analysis analyzes the association between patients' lipid profiles and CAD-RADS scores. P-value <0.05 was considered statistically significant. Results: A total of 543 (274 female) patients were included in this study. In the univariate analysis, the LDL/HDL ratio was significantly associated with the severity of CAD based on CAD-RADS scores. The multivariate analysis revealed that the LDL/HDL ratio was the most significant lipid parameter across all models (Adj OR: 9.728, 95% CI: 2.078-45.649, P = 0.004), with the highest adjusted odds ratio observed after adjustments for age, gender, family history, history of hypertension, diabetes mellitus, and chronic kidney disease, and also smoking status. The LDL/HDL ratio cut-off value was 2.82 with a sensitivity of 83.95% and a specificity of 21.05%. Other non-traditional lipid profiles lost their significance in the multivariate models. Conclusions: The LDL/HDL ratio was significantly associated with obstructive CAD, as assessed by the CAD-RADS score, even after adjustment for other cardiovascular risk factors